Pemetaan Usaha Kelompok Ternak Menggunakan Model Bisnis Kanvas Pada Sekolah Peternakan Rakyat (SPR) Di Kabupaten Muara Enim - Andi Nurmala Suardi; Eko Ruddy Cahyadi; Abdul Basith (Journal of Food System & Agribusiness, 2018)
ABSTRACTÂ The business carried out by livestock groups on the SPR is currently very limited. Livestock groups need strategies to develop their livestock groups with SPR. Strategy requires mapping activities to be done to realize the goals SPR wants to achieve with livestock groups. Mapping livestock business groups mapped using a canvas business model. The business model of the canvas has 9 elements that must be filled in accordance with the current conditions owned by the cattle group with the SPR. The mapping of the development effort to be carried out is also poured into the canvas business model to see what a group needs in its development. Based on the mapping results there are several products, activities and additional resources that must be owned by livestock groups with SPR. In addition, costs and sources of income also increase along with the increase of products offered to customers.Â Keywords: business development , groups of livestock, SPR, the business model canvas